Bladder Symptoms in Children With Functional Constipation: A Systematic Review. Issue 5 (November 2018) - van Summeren, Jojanneke J.G.T.; Holtman, Gea A.; van Ommeren, Sonja C.; Kollen, Boudewijn J.; Dekker, Janny H.; Berger, Marjolein Y.
ABSTRACT: Objective: The aim of the review is to perform a systematic review of the literature examining the prevalence of bladder symptoms in children with functional constipation (FC) and to compare the prevalence of those symptoms between children with and without FC. Methods: In this systematic review 4 databases were searched to July 2018. Studies investigating the prevalence of bladder symptoms in children aged 4 to 17 years with FC were included. There was no language restriction. Two reviewers independently extracted data and assessed study quality. Clinical heterogeneity between studies was investigated. Prevalence rates of bladder symptoms in children with FC were calculated. Relative risks were calculated to compare the prevalence of bladder symptoms between children with and without FC. Results: Among 23 studies of children with FC, 22 reported the prevalence bladder symptoms (12, 281 children) and 7 reported the prevalence of urinary tract infections (UTIs) (687 children). The prevalence rates of single bladder symptoms, lower urinary tract symptoms (LUTS), and UTI varied between 2% to 47%, 37% to 64%, and 6% to 53%. The relative risks were 1.24 to 6.73 for 20 single bladder symptoms (12 studies) and 2.18 to 6.55 for UTI (2 studies). The 95% confidence intervals indicated significance in 14 of 20 single bladder symptoms. Conclusions: Bladder symptoms seem common in children with FC, but the reported prevalence varies greatly. Children with FC are more likely to have bladder symptoms than children without FC. We recommend that clinicians be aware of concomitant bladder symptoms in children presenting with FC. Abstract : Supplemental Digital Content is available in the text